A Low-Cost Arduino-Based Ultrasonic System for Shallow-Water Wave Characterization - Humairah, Nur Aisyah; Rosman N, Andi; Yahya, Amran; Hutapea, Bilferi; Amir, Faizal; Nurlina, Nurlina (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2026)
Accurate measurement of shallow-water waves is essential for understanding wave propagation and fluid dynamics in physics education and laboratory research. However, quantitative wave experiments are often constrained by the high cost and complexity of commercial measurement systems. This study developed and evaluated a low-cost Arduino-based ultrasonic measurement system for investigating shallow-water wave characteristics under controlled laboratory conditions. A dual-sensor configuration employing HC-SR04 ultrasonic sensors was used to record real-time water-surface fluctuations generated at different excitation frequencies. The recorded signals were processed to determine wave amplitude and propagation velocity, and the experimental results were compared with theoretical shallow-water wave predictions. The system successfully captured frequency-dependent variations in wave behavior and produced propagation velocities that closely agreed with theoretical expectations, demonstrating satisfactory measurement performance despite minor deviations attributable to sensor resolution, boundary reflections, and experimental uncertainties. The observed wave responses also suggested frequency-dependent changes in energy transfer, although resonance mechanisms require further investigation. Overall, the developed system demonstrates the feasibility of using low-cost open-source instrumentation for quantitative shallow-water wave experiments. Beyond its research potential, the platform offers an accessible laboratory resource that integrates physics experimentation, programming, electronics, and data analysis, making it well suited for STEM-oriented and project-based physics learning.